2019
DOI: 10.3389/fpls.2019.01601
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Nitrogen Nutrition Status in Winter Wheat From Unmanned Aerial Vehicle Based Multi-Angular Multispectral Imagery

Abstract: Rapid, non-destructive and accurate detection of crop N status is beneficial for optimized fertilizer applications and grain quality prediction in the context of precision crop management. Previous research on the remote estimation of crop N nutrition status was mostly conducted with ground-based spectral data from nadir or oblique angles. Few studies investigated the performance of unmanned aerial vehicle (UAV) based multispectral imagery in regular nadir views for such a purpose, not to mention the feasibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 63 publications
2
27
0
1
Order By: Relevance
“…To monitor the crop growth indicators, several researchers have used UAVs equipped with hyperspectral cameras, multispectral cameras, and lidars [14,[45][46][47]. Although such monitoring reflected the growth status of the vegetation, it was not easy to popularize and apply due to its high cost.…”
Section: Feasibility Of Monitoring Rice Growth Indicators Using Uavsmentioning
confidence: 99%
See 1 more Smart Citation
“…To monitor the crop growth indicators, several researchers have used UAVs equipped with hyperspectral cameras, multispectral cameras, and lidars [14,[45][46][47]. Although such monitoring reflected the growth status of the vegetation, it was not easy to popularize and apply due to its high cost.…”
Section: Feasibility Of Monitoring Rice Growth Indicators Using Uavsmentioning
confidence: 99%
“…RS based on the UAV technology has great potential for monitoring rice LDF, LAI, and leaf nitrogen accumulation [13]. Some studies have used UAVs equipped with multispectral cameras to assess the crop growth status and estimate yield, indicating that the application of UAVs to crop monitoring had the advantages of timeliness, high resolution [14][15][16], and multiband index combination [17]; however, high resolution RS is very expensive for the small scale farmers, and only big farmers, which represent only a small percent of the farmers worldwide, get benefits from its use [18]. Therefore, using low-cost UAVs to obtain RGB images to monitor crop-growth indicators and exploring the feasibility of this application in agriculture is an important research direction [2,19].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen is an essential macronutrient that promotes plant development and crop yield and quality [27][28][29][30]. Many studies have claimed that N is an essential element involved in the biosynthesis of chlorophyll [31], nucleic acids [32], amino acids [33], and enzymes [34], which are associated with the accumulation of plant nutrients [35,36]. In addition, N is the key factor for the metabolism of plant secondary chemicals, such as phytohormones (e.g., abscisic acid, ABA; indole-3-acetic acid, IAA; cytokinin, CK) [37,38], polyphenolics, tannins, and flavonoids [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Recall that Model IV included an additional explanatory variable, namely the camera azimuth angle from the plot center to the camera, could be proved to improve model fit. We observed that recent studies have confirmed that the reflectance observed by UAS are affected by multiple solar angles (Assmann et al, 2018) and camera view angles (Cheng et al, 2019). Compared to previous research, the multispectral images were not collected by the UAS at multiple discrete camera view angles intentionally in this study.…”
Section: Model III Vs Ivmentioning
confidence: 78%